FAMILY AND COMMUNITY SOCIAL CONTROL AGAINST THE INCREASE IN POSITIVE CASES OF COVID 19 CHILDREN, JAGAKARSA VILLAGE, SOUTH JAKARTA - Paisal Halim; Elisa Rizka Adriani (JILPR Journal Indonesia Law and Policy Review, 2022)
This study aims to find out how the role of families and the community in preventing and controlling the increase in cases of positive COVID-19 children in the Jagakarsa village, as well as what obstacles are experienced by families and communities in overcoming the increase in COVID-19 cases and what efforts are being made by families and communities to reduce the increase in cases. This study uses qualitative methods with data collection techniques, namely interviews. Determination of the sources in this study by purposive sampling, namely the family and the community, namely Dasawisma mothers and people who live in Jagakarsa Village. The form of social control is seen from the point of view of Travis Hirschi. namely: 1. Attachment (love), namely social control starting from the family by providing a sense of security through limiting children to join gatherings outside the home and obeying health protocols with masks, washing hands and avoiding crowds..2. Involvement (involvement), namely being pro-active in the community in preventing, handling, and controlling Covid-19 cases. 3. Commitment (responsibility) is the responsibility of the community to remind each other about health protocols. 4. Belief, namely the public's belief about the dangers of Covid-19 can control people's behavior. The steps taken by local residents are providing understanding and knowledge about Covid-19, dropping off and picking up children to school, giving traditional herbal medicine, fulfilling balanced nutrition and limiting curfew activities, eliminating crowding activities and vaccinating local residents.